2011
DOI: 10.1126/scisignal.2001682
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide-Based Target Screen Implicates the Protein Kinase CK2 in the Global Regulation of Caspase Signaling

Abstract: The convergence of caspase and protein kinase signaling pathways has become increasingly evident, as illustrated by the protection of caspase substrates from cleavage upon undergoing phosphorylation at or near to their caspase recognition motifs. To investigate the global role of phosphorylation in the regulation of caspase signaling, we designed a peptide match program to identify sequences from the human proteome that contained overlapping recognition motifs for caspases and kinases. We identified the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 65 publications
(81 reference statements)
3
80
0
Order By: Relevance
“…Building on these observations, a combined computational and biochemical approach revealed an extensive repertoire of proteins with overlapping CSNK2 and caspase recognition motifs suggesting that CSNK2 could have widespread impact on caspase action (15). In addition to the identification of many proteins known to be caspase substrates, these studies also demonstrated that CSNK2 could phosphorylate CASP3 CSNK2 has been implicated in a diverse array of biologic processes.…”
Section: Convergence Of Csnk2 With Caspase Pathwaysmentioning
confidence: 90%
“…Building on these observations, a combined computational and biochemical approach revealed an extensive repertoire of proteins with overlapping CSNK2 and caspase recognition motifs suggesting that CSNK2 could have widespread impact on caspase action (15). In addition to the identification of many proteins known to be caspase substrates, these studies also demonstrated that CSNK2 could phosphorylate CASP3 CSNK2 has been implicated in a diverse array of biologic processes.…”
Section: Convergence Of Csnk2 With Caspase Pathwaysmentioning
confidence: 90%
“…Along with the DNA repair response, CK2 positively regulates an extensive list of additional cellular processes that are also established effectors of sensitivity to DNAtargeted chemotherapeutics as well as other anticancer drugs, including PI3K/AKT/mTOR signaling, NF-kB transcription, Hsp90 machinery activity, hypoxia, inhibition of apoptosis, and IL-6 expression (3,(8)(9)(10)(11). Indeed, sensitization of pancreatic cancer cells to gemcitabine and head and neck cancer cells to cisplatin by genetic manipulation of CK2 expression has been attributed to resulting suppression of Akt and NF-kB activity, respectively (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Recently validated as an anticancer drug target, CK2 regulates a diverse array of prosurvival cellular processes, including epidermal growth factor receptor signaling, PI3K/AKT/mTOR signaling, Hsp90 machinery, hypoxia, and interleukin (IL)-6 expression, all of which play important roles in resistance to various chemotherapeutics (3,4,(8)(9)(10)(11). Furthermore, protein kinase CK2 has emerged as a key participant in DNA repair response, being essential for the surveillance and repair of both single and double strand breaks (6).…”
Section: Introductionmentioning
confidence: 99%
“…The beads were resuspended in 250 μl of 2X caspase assay buffer containing 20 mM dithiothreitol (DTT) and preheated at 37 °C for 15 min to optimize enzymatic reactions. Activated caspase 3 and caspase 7 (500 nM) generated as described by Duncan et al 44 were incubated with the preheated mixture at 37 °C for 1 h. Samples were centrifuged (4500 rpm for 2 min) washed 2 times with 1X caspase assay buffer, mixed with 2X Laemmli loading buffer, boiled for 5 min, and western blotted. Blots were probed with C-terminal antibodies, washed, and probed with secondary antibodies to verify the presence of caspase cleavage as described above.…”
Section: Cell-free Caspase Assaymentioning
confidence: 99%